PENGGUNAAN MEDIA PEMBELAJARAN DIORAMA 3 DIMENSI PADA MATERI KEANEKARAGAMAN BUDAYA INDONESIA TERHADAP HASIL BELAJAR SISWA KELAS IV MI SABILUL MUBTADIIN - Rifayanti, Zuni Eka (FKIP Unirow Tuban, 2021)
The objectives of this study are to: (1) describe the use of 3-dimensional diorama learning media on the diversity of Indonesian ethnic groups, (2) analyze and describe student learning outcomes using 3-dimensional diorama media, material on the diversity of Indonesian ethnic groups in grade IV MI Sabilul. Mubtadiin Randegansari. The research method used is descriptive qualitative research with the subject of grade IV students. Data collection techniques using interviews, tests, and documentation. Data analysis techniques are carried out in research through data reduction, data presentation, and drawing conclusions. The technique of testing the validity of the data was carried out by extending observations, increasing persistence, triangulation, and reference materials. The results of the study prove that the use of 3-dimensional diorama media can affect student learning outcomes with an average score of 70.6 to 91.15. The improvement of learning outcomes is carried out through 3 stages, namely a. the preparation stage, namely preparing teaching materials, b. the development stage, namely the provision of learning videos, and c. the learning stage, where students answer a question in the video, then are given the pretest and posttest questions.